Current practice in the field of architectural and autonomous stained glass in Europe and the United States of America - Nesbit, G H H (Rhodes University, Faculty of Humanities, Department of Fine Art, 1987)
This prodrome sought to define through research, the material. composition, historic foundations, significance and technical development of glass as a window-glazing material for ecclesiastical, and later secular purposes, and examining thus its determining role in the development of architecture. The history and techniques of stained glass, an art-form linked more than any other to the mythology and dogma of the Roman Catholic Church, were traced; its history is thus one with that of the church, rising to its greatest glory during the twelfth and thirteenth centuries, and declining from the late fifteenth to the seventeenth centuries. The iconography of the church was examined, and the development of window and tracery types discussed through reference to pertinent examples on both sides of the English Channel. Subjects, stylistic and technical factors, sources of reference, ecclesiastical influences, were all within the context of social and political history . viewed. Intro., p. 1-2.
Keywords: Glass painting and staining -- Europe; Glass painting and staining -- United States